1976
DOI: 10.1037/0097-7403.2.4.342
|View full text |Cite
|
Sign up to set email alerts
|

Aversions to unflavored water and cup drinking produced by delayed sickness.

Abstract: Rats drank from a cup and were then injected with lithium chloride. The result was an apparent association between the appearance of the cup and toxicosis. In Experiment 1, avoidance of drinking unflavored water from the cup was apparent after two trials in which toxicosis was induced either immediately or 1/2 hr. after such drinking. Consumption of sucrose solution from the cup prior to toxicosis, however, did not produce a statistically reliable aversion to drinking unflavored water from the cup. In Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
1

Year Published

1977
1977
1990
1990

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 22 publications
4
15
1
Order By: Relevance
“…In contrast to previous reports of failures to obtain evidence of conditioning when exteroceptive CSs are paired with interoceptive USs (Garcia & Koelling, 1966, 1967Garcia, McGowan, Ervin, & Koelling, 1968), more recent research has shown that relatively novel exteroceptive cues will acquire aversive properties when paired with an interoceptive US (Best, Best, & Mickley, 1973;Mitchell, Kirschbaum, & Perry, 1975;Revusky & Parker, 1976;Rozin, 1969, Experiment 3). However, the fact that exteroceptive cues have been found to acquire relatively little aversiveness if the CS-US interval is a matter of hours (Revusky & .Garcia, 1970;Revusky & Parker, 1976) or if the exteroceptive cue is presented in compound with a flavor cue (Best et al, 1973;Revusky & Parker, 1976) might be interpreted as providing support for a weak form of what Bitterman (1975Bitterman ( , 1976 has termed the "associative predisposition" hypothesis: although animals readily associate exteroceptive cues with an interoceptive US, they are even more prepared to associate interoceptive cues with an interoceptive US.…”
contrasting
confidence: 44%
See 1 more Smart Citation
“…In contrast to previous reports of failures to obtain evidence of conditioning when exteroceptive CSs are paired with interoceptive USs (Garcia & Koelling, 1966, 1967Garcia, McGowan, Ervin, & Koelling, 1968), more recent research has shown that relatively novel exteroceptive cues will acquire aversive properties when paired with an interoceptive US (Best, Best, & Mickley, 1973;Mitchell, Kirschbaum, & Perry, 1975;Revusky & Parker, 1976;Rozin, 1969, Experiment 3). However, the fact that exteroceptive cues have been found to acquire relatively little aversiveness if the CS-US interval is a matter of hours (Revusky & .Garcia, 1970;Revusky & Parker, 1976) or if the exteroceptive cue is presented in compound with a flavor cue (Best et al, 1973;Revusky & Parker, 1976) might be interpreted as providing support for a weak form of what Bitterman (1975Bitterman ( , 1976 has termed the "associative predisposition" hypothesis: although animals readily associate exteroceptive cues with an interoceptive US, they are even more prepared to associate interoceptive cues with an interoceptive US.…”
contrasting
confidence: 44%
“…However, the fact that exteroceptive cues have been found to acquire relatively little aversiveness if the CS-US interval is a matter of hours (Revusky & .Garcia, 1970;Revusky & Parker, 1976) or if the exteroceptive cue is presented in compound with a flavor cue (Best et al, 1973;Revusky & Parker, 1976) might be interpreted as providing support for a weak form of what Bitterman (1975Bitterman ( , 1976 has termed the "associative predisposition" hypothesis: although animals readily associate exteroceptive cues with an interoceptive US, they are even more prepared to associate interoceptive cues with an interoceptive US. But proponents of general-process learning theory (e.g., Krane & Wagner, 1975) might argue that such findings simply reflect differences in the qualitative properties of exteroceptive and interoceptive cues (e.g., differences in trace persistence, susceptibility to interference, relative novelty, etc.…”
mentioning
confidence: 99%
“…However, this selective association of taste with toxicosis does not preclude the learning of aversions to other types of cues as well. Toxicosis-induced aversion learning in rats has been demonstrated with spatial, environmental cues (e.g., Krane, 1980), visual stimuli (Braveman, 1977;Galef & Osborne, 1978), olfactory stimuli (e.g., Rusiniak et al, 1979), the temperature of water (Nachman, 1970), cues of drinking from a cup (Revusky & Parker, 1976), and cues of drinking from spouts with large or small openings (Nachman, Rauschenberger, & Ashe, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…with taste stimuli can occur even if the toxicosis is delayed for an hour or more following exposure to the CS flavor (e.g., Revusky & Garcia, 1970). In the present study, independent groups of rats were injected with lithium 0, 30, 60, and 120 min after access to familiar food in novel metal sleeves.…”
Section: Methodsmentioning
confidence: 99%
“…For example, rats will learn to run at different speeds in a runway for different sucrose concentrations (e.g., see Collier & Marx, 1959;Flaherty, Riley, & Spear, 1973); bees demonstrate a variety of associative phenomena with exteroceptive stimuli paired with sucrose solutions (Bitterman, 1988;Couvillon & Bitterman, 1984); contextual stimuli may modulate conditioned taste aversions (e.g., see Revusky & Parker, 1976), although cues closely correlated with the taste substance, such as the bottle or nozzle, are apparently more potent than other apparatus-related stimuli (Archer, Sjoden, & Nilsson, 1985); and, in our own situation, context-taste associations are indicated by differential latencies to initiate licking as a function of sucrose or saccharin concentration differences (e.g., Czachowski, Weaver, & Flaherty, 1989;Flaherty & Grigson, 1988). Thus, even though rats may readily form associations between taste stimuli and contextual cues, these associations CONTEXT AND CONTRAST 275 are apparently not necessary for the comparison of reward value across different contexts.…”
Section: Discussionmentioning
confidence: 99%